CARE FOR SOCIAL LIFE HARMONY IN A MULTICULTURAL COMMUNITY (Field Study in Haekriit Settlement, Manleten Village, East Tasi Feto District, Belu - NTT) - Joseph Uskono; Emanuel Tati Taena; Alphonsus Maria de Liguori Sakunab (Jurnal Scientia, 2023)
Indonesia is a country whose society is very plural. This plural reality is certainly a challenge in maintaining a harmonious social life between communities. Because caring for a harmonious social life is not as easy as theorizing, giving speeches, arguing or having an opinion. Maintaining harmony in social life in a pluralistic society requires an awareness that is truly born from a natural urge to be aware of one's own identity and to have the courage to accept the differences that exist in others. Social life in harmony in the context of a multicultural society is an important condition to be built and maintained. Mutual respect, respect and acceptance of one another is very much needed for the creation of a peaceful, just and prosperous society. Differences in culture, race, ethnicity, culture should be seen as abundance and wealth that must be accepted and cared for in living together with other people. The community in the Haekriit settlement is one of the bases for reflecting and learning about how to care for the harmony of social life in the community. Plurality is not an obstacle for the community. They live in peace, harmony, harmony even though their community face is very heterogeneous and plural. The culture and traditions of each small group that were brought with them from Timor Leste were not simply abandoned or competed with the culture and traditions of the group, but were cared for, guarded and passed down from generation to generation to the next generation in peace and harmony.